(untitled) (Revista Rupturas, 2017)
The gradual decrease in the amount of water sources in the Central County of Puntarenas has given way to conflicts during the last few years. Therefore, people in the affected communities have become organized and have taken action to change the current unjust method of water distribution and usage. In this article, the work of the author inregards to this conflict within these community organizations which started in 2013 is described. The emphasis will be given on the conflict around the community of Guacimal. This particular conflict has evidenced all the various issues that communities face during their defense of this resource in the current government model of water management.